(untitled) (Journal of the College of Basic Education, 2022)
Summary:Concepts and theories are characterized by the specificity of resolving the complexities of expressions circulating in design in particular, including analysis and composition (redesign), which are among the basics of philosophical thought on which the design process is based, including the brand as an identity and a message that dialogues with the recipient and the consumer. It is linked to the factors of influencing and effective forces to form it, such as creativity, perception, understanding and imagination on the one hand, and on the other hand culture, thought, values ​​and communication.